Caminhos, trilhas e cartografias quilombolas de Chapada dos Guimarães (MT) - Kamikiawa, Cassiana Oliveira da Silva (2021)
This dissertation was developed with the Ribeirão Itambé Quilombola Community, located in the municipality of Chapada dos Guimarães in Mato Grosso, and seeks to map the networks of relationships that connect quilombola families. The anthropological work was designed through some paths, embrancing field experiences to theoretical reflections. In this regard, I present the anthropological implications around the quilombola issue, as if I were composing the paths that these subjects conceive, perceive and produce their territories, as well as the tensions that involves temporal, sociocultural and political processes. The research process is guided by the recognition of the plurality of voices that compose the ethnographic scene and the ethical commitment to the subjects of this dialogue. The field work demonstrated greater fluidity in the social organization of these territories, once the quilombolas of Ribeirão Itambé organize themselves through a network of kinship and compadrio relationships, celebrations of saint festivities and family gatherings. Resignifying the environments, they rework an expanded territoriality through the flows that permeate and interconnect them to the traditional territory. And in this flow, the community of Ribeirão Itambé challenges the State and society, claiming rights to the title of their territories and the recognition of their existence.